2015
DOI: 10.1186/s12887-015-0385-9
|View full text |Cite
|
Sign up to set email alerts
|

Presence of anti-Toxocara canis antibodies and risk factors in children from the Amecameca and Chalco regions of México

Abstract: BackgroundToxocariasis is a zoonotic disease that poses a threat to public health worldwide. This disease primarily affects children and is caused by the presence in the digestive tract of a common roundworm of dogs, Toxocara canis, or cats, Toxocara cati. Toxocara is responsible for the presentation of various syndromes in humans depending on the affected organs.MethodsIn this study, the prevalence of anti-T. canis antibodies was investigated in children aged 3–16 years from semirural populations in the munic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
2
7
0
4
Order By: Relevance
“…All subsequent studies support Beaver's observation. Although in most populations studied young children have exhibited the highest prevalence [ 21 23 ] some studies have failed to show the age-related correlation [ 1 , 24 , 25 ]. Toxocariasis predominantly affects the children due to their close contact with pet animals (dogs and cats), geophagia, poor hygienic practices, and playing in contaminated sand pits.…”
Section: Discussionmentioning
confidence: 99%
“…All subsequent studies support Beaver's observation. Although in most populations studied young children have exhibited the highest prevalence [ 21 23 ] some studies have failed to show the age-related correlation [ 1 , 24 , 25 ]. Toxocariasis predominantly affects the children due to their close contact with pet animals (dogs and cats), geophagia, poor hygienic practices, and playing in contaminated sand pits.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors include young age, low socioeconomic status, poor hygiene, eating without washing hands, nail biting, owning dogs or cats, low levels of parental education, playing in sandpits, or eating raw or undercooked meat containing encapsulated larvae from domestic animals such as chickens, pigs, sheep, or cows. 1,[6][7][8] Hoffmeister et al 9 identified a case of cerebral toxocariasis caused by the consumption of raw duck liver which is usually one of the most heavily affected organs in toxocariasis because it drains portal venous blood containing large amounts of larvae after oral uptake. Some human infections may occur by ingestion of contaminated dog fur.…”
Section: Risk Factorsmentioning
confidence: 99%
“…En México sólo existen reportes bibliográficos de casos aislados de infección por larva migrans ocular y larva migrans visceral, que no indican la magnitud del problema. Sin embargo, en estudios serológicos recientes se han reportado prevalencias del 22.22 % en Ecatepec, Estado de México (Romero 2013), de 26.2 % en la población rural Tepehuanos, Durango (Alvarado-Esquivel 2014), y de 12.02 % en Amecameca y Chalco, Estado de México (Nava 2015). Es importante destacar que dichas prevalencias demuestran la exposición de las personas al parásito, más no el desarrollo de la enfermedad.…”
Section: Introductionunclassified